Brain endurance training as a strategy for reducing mental fatigue - André, N.; Audiffren, M.; Englert, C. (Frontiers in Psychology, 2025)
Mental fatigue is a psychobiological state triggered by sustained mental effort, affecting subjective parameters, performance, and physiological responses. It impairs sports performance across various disciplines. Individual differences in mental fatiguability and physical fitness may moderate the effects of mental fatigue. Initial evidence suggests that endurance athletes are more resilient to the decrease in the capacity and/or willingness to deploy mental effort induced by mental fatigue, though the results are mixed. Brain Endurance Training (BET) aims to enhance resistance to mental fatigue by combining cognitive and physical training. BET typically uses dual-task designs (simultaneous mental and physical effort), which appear more effective than sequential-task designs. Cognitive tasks involved in brain endurance training often target executive functions, like sustained attention and inhibitory control. While BET consistently improves endurance performance, its effects on subjective mental fatigue are currently less conclusive, which offers intriguing possibilities for future research. Other outcomes, such as perceived exertion and brain oxygenation, suggest BET reduces the cognitive cost of mental and physical effort. BET may also influence brain networks related to attention and self-regulation, particularly the salience network, default mode network (DMN), and frontoparietal network (FPN). Functional connectivity studies hint that BET could lead to beneficial changes in how these networks interact, potentially reducing DMN activity and enhancing control by task-positive networks. Although evidence is still emerging, early findings support BET as a promising intervention to reduce the likelihood of getting mentally fatigued and improve endurance performance in cognitively demanding contexts. Future research should refine BET protocols and explore its underlying neural mechanisms using imaging techniques.